The Effect of Heavy Ions on the Dispersion Properties of Kinetic Alfvén Waves in Astrophysical Plasmas - Lopez-Escobar, R (EDP Sciences, 2023)
Context. Spacecraft measurements have shown Kinetic Alfvén Waves propagating in the terrestrial magnetosphere at lower wave-normal angles than predicted by linear Vlasov theory of electron-proton plasmas. To explain these observations, it has been suggested that the abundant heavy ion populations in this region may have strong, non-trivial effects that allow Alfvénic waves to acquire right-handed polarization at lower angles with respect to the background magnetic field, as in the case of typical electron-proton plasma. Aims. We study the dispersion properties of Alfvénic waves in plasmas with stationary phase-space distribution functions with different heavy ion populations. Our extensive numerical analysis has allowed us to quantify the role of the heavy ion components on the transition from the left-hand polarized electromagnetic ion-cyclotron (EMIC) mode to the right-hand polarized kinetic Alfvén wave (KAW) mode. Methods. We used linear Vlasov-Maxwell theory to obtain the dispersion relation for oblique electromagnetic waves. The dispersion relation of Alfvén waves was obtained numerically by considering four different oxygen ion concentrations ranging between 0.0 and 0.2 for all propagation angles, as a function of both the wavenumber and the plasma beta parameter. Results. The inclusion of the heavy O+ ions is found to considerably reduce the transition angle from EMIC to KAW both as a function of the wave number and plasma beta. With increasing O+ concentrations, waves become more damped in specific wavenumber regions. However, the inclusion of oxygen ions may allow weakly damped KAW to effectively propagate at smaller wave-normal angles than in the electron-proton case, as suggested by observations. © 2023 Authors.